Geoparks and territorial identity: A study of the spatial affinity of inhabitants with UNESCO Geopark De Hondsrug, The Netherlands. (May 2019) - Stoffelen, Arie; Groote, Peter; Meijles, Erik; Weitkamp, Gerd
Abstract: Even though the societal and academic attention to geoparks is on the rise, there is a distinct absence of studies on communities and their perceptions of the landscapes institutionalized by geoparks. This paper contributes to the geopark literature by problematizing the geographical awareness, landscape associations and territorial identities of geopark inhabitants. Using a quantitative case study of UNESCO Geopark De Hondsrug (the Netherlands), the paper shows a complex image regarding the inhabitants' affinity with their living environment. At its initiation, the geopark did not build on the landscape associations of local inhabitants. Composite overlap mapping of mental maps drawn by inhabitants shows that the geopark incorporates an area that is substantially larger than the area interpreted by the inhabitants as constituting the Hondsrug. Nevertheless, the core area of the Hondsrug is recognized and lived by the majority of the people, providing a starting point for improving the community's support for the geopark's brand. We conclude that only when there is enough bottom-up recognition and embedding of the brand and its underlying landscape values, a geopark's narrative can be effectively built on for endogenous regional development purposes. Highlights: We study geopark inhabitants' landscape associations and territorial identity. We use mental maps and scale-based surveys in UNESCO Geopark De Hondsrug, Netherlands. At its initiation, the geopark did not build on its inhabitants' landscape values. There is consensus about the core of the Hondsrug region and its compass direction. Only with community embeddedness, geoparks can be used for regional development.